Nanowire-based sensor electronics for chemical and biological applications. Issue 22 (20th October 2021) - Zhang, Guozhu; Zeng, Hao; Liu, Jiangyang; Nagashima, Kazuki; Takahashi, Tsunaki; Hosomi, Takuro; Tanaka, Wataru; Yanagida, Takeshi
Abstract : Detection and recognition of chemical and biological species via sensor electronics are important not only for various sensing applications but also for fundamental scientific understanding. Abstract : Detection and recognition of chemical and biological species via sensor electronics are important not only for various sensing applications but also for fundamental scientific understanding. In the past two decades, sensor devices using one-dimensional (1D) nanowires have emerged as promising and powerful platforms for electrical detection of chemical species and biologically relevant molecules due to their superior sensing performance, long-term stability, and ultra-low power consumption. This paper presents a comprehensive overview of the recent progress and achievements in 1D nanowire synthesis, working principles of nanowire-based sensors, and the applications of nanowire-based sensor electronics in chemical and biological analytes detection and recognition. In addition, some critical issues that hinder the practical applications of 1D nanowire-based sensor electronics, including device reproducibility and selectivity, stability, and power consumption, will be highlighted. Finally, challenges, perspectives, and opportunities for developing advanced and innovative nanowire-based sensor electronics in chemical and biological applications are featured.